2016
DOI: 10.1111/mec.13757
|View full text |Cite
|
Sign up to set email alerts
|

A portrait of a sucker using landscape genetics: how colonization and life history undermine the idealized dendritic metapopulation

Abstract: Dendritic metapopulations have been attributed unique properties by in silico studies, including an elevated genetic diversity relative to a panmictic population of equal total size. These predictions have not been rigorously tested in nature, nor has there been full consideration of the interacting effects among contemporary landscape features, colonization history and life history traits of the target species. We tested for the effects of dendritic structure as well as the relative importance of life history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 131 publications
1
16
1
Order By: Relevance
“…Heightened upstream genetic structure and DIGD is particularly pronounced in organisms inhabiting dendritic systems with many confluences and larger ranges (Crispo, Bentzen, Reznick, Kinnison, & Hendry, ; Ginson et al, ; Salisbury, McCracken, Keefe, Perry, & Ruzzante, ; Thomaz et al, ); however, linear river systems do not typically show strong signals of reduced upstream gene flow (Kanno et al, ; Paz‐Vinas et al, ; Thomaz et al, ). Thomaz et al () found a signal of DIGD in linear systems, but their models are based on a total range of 1,000 km, which suggests that a detectable signal of downstream‐biased dispersal (and the associated effects of DIGD and higher genetic differentiation in upstream areas) may not exist at smaller spatial scales such as that of E. lemniscatum (~38 km).…”
Section: Discussionmentioning
confidence: 99%
“…Heightened upstream genetic structure and DIGD is particularly pronounced in organisms inhabiting dendritic systems with many confluences and larger ranges (Crispo, Bentzen, Reznick, Kinnison, & Hendry, ; Ginson et al, ; Salisbury, McCracken, Keefe, Perry, & Ruzzante, ; Thomaz et al, ); however, linear river systems do not typically show strong signals of reduced upstream gene flow (Kanno et al, ; Paz‐Vinas et al, ; Thomaz et al, ). Thomaz et al () found a signal of DIGD in linear systems, but their models are based on a total range of 1,000 km, which suggests that a detectable signal of downstream‐biased dispersal (and the associated effects of DIGD and higher genetic differentiation in upstream areas) may not exist at smaller spatial scales such as that of E. lemniscatum (~38 km).…”
Section: Discussionmentioning
confidence: 99%
“…Access to this watershed may have been enhanced by significant runoff from the paleolake Naskaupi, which drained through the Kogaluk between 7,500 and 6,000 years BP (Barnett & Peterson, ; Jansson & Kleman, ). Alternatively, many lakes within the Kogaluk River drainage are connected via shallow streams which could facilitate the occasional migration between lakes as it has for lake trout (McCracken, Perry, Keefe, & Ruzzante, ) and longnose suckers ( Catostomus catostomus ) (Salisbury, McCracken, Keefe, Perry, & Ruzzante, ) in this system. Migration may have countered genetic drift (Tallmon, Luikart, & Waples, ), maintaining both Arctic and Atlantic lineage haplotypes in these lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonequilibrium metapopulation dynamics and colonization history may also exert stronger influence over species genetic patterns than network architecture (in fish Salisbury et al . ; salamanders Cosentino et al . ).…”
Section: Introductionmentioning
confidence: 99%